Things get better - Piper, Katie (Quercus, 2012)
Katie Piper knows just what it's like to pull yourself up from rock bottom, and her recovery from a rape and acid attack is nothing short of astonishing. She has become a orle model for positive thinking and has received countless letters and emails from people just like you who are going through everything from break-ups, eating disorders, job loss and coming out, to recovery from issues such as violence, disfigurement or abuse. In 'Things Get Better', Katie revisits each stage of her own recovery and shows that you are not alone in your feelings. She explains how to take things one day at a time to find happiness and contentment, and reveals how to stay positive nd treat yourself with the kindness you deserve. Katie is determined to show that there is a way forward through your darkest times, and it all starts with you. If you believe, you will survive.